Social participation and diabetes control in Cypriot adults A cross-sectional study - Chrysostomou, Stavri; Andreou, Sofia N. (My University, 2023)
OBJECTIVE To examine the association between dietary behavior, social engagement and participation, and diabetes control among Cypriot adults with diabetes mellitus (DM). METHOD Adults aged between 18 and 75 years, diagnosed with DM, type 1 or type 2, were eligible for inclusion in the study. A questionnaire on general sociodemographic data, and health, nutritional and social factors was administered. The primary outcome was diabetes control as assessed by the mean fasting glucose (FG) levels of the last 3 months. RESULTS The sample consisted of 297 adults (59% men and 41% women), with an average age of 60.9 years (range 19–73 years), most of whom were married with children. More than half of the participants (61.6%) had mean FG levels above the normal levels (i.e. >126 mg/dL). Increased age was associated with a 0.8% lower risk of uncontrolled DM (p<0.05). Higher income was associated with a 3.8% lower risk (p<0.05), and increased exercise with a 3% lower risk (p<0.05) of uncontrolled DM. Higher frequency of going out for food was associated with a 5.5% higher risk of uncontrolled DM (p<0.05). With regard to personal beliefs, believing that DM affects social participation was associated with a 5.8% higher risk (p[removed]
Keywords: Diabetes control; Diabetes mellitus; Dietary behavior; Social engagement; Social participation